2006
DOI: 10.1111/j.1744-7348.2005.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf chlorophyll concentration relates to transpiration efficiency in peanut

Abstract: Two pot experiments were conducted in two different seasons at the University of Agricultural Science, Bangalore, India, to study (a) the relationship between chlorophyll concentration (by measuring the leaf light-transmittance characteristics using a SPAD metre) and transpiration efficiency (TE) and (b) the effect of leaf N on chlorophyll and TE relationship in peanut. In Experiment (Expt) I, six peanut genotypes with wide genetic variation for the specific leaf area (SLA) were used. In Expt II, three non-nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 25 publications
6
75
1
Order By: Relevance
“…The latter would combine water saving with high yield potential, but is considered to be less variable in plants beyond different photosynthetic pathways. Leaf chlorophyll concentration (Rao et al 2001;Sheshshayee et al 2006) and specific leaf area (Rao et al 1995;Richards 2000), however, are proxies for selection of genotypes with high intrinsic water-use efficiency mediated by superior photosynthetic capacity. Measurement of leaf temperature has been used as a screening trait for sustained plant water supply (Blum et al 1982) instead of direct measurement of stomata conductance.…”
Section: Breeding For Dehydration Avoidancementioning
confidence: 99%
“…The latter would combine water saving with high yield potential, but is considered to be less variable in plants beyond different photosynthetic pathways. Leaf chlorophyll concentration (Rao et al 2001;Sheshshayee et al 2006) and specific leaf area (Rao et al 1995;Richards 2000), however, are proxies for selection of genotypes with high intrinsic water-use efficiency mediated by superior photosynthetic capacity. Measurement of leaf temperature has been used as a screening trait for sustained plant water supply (Blum et al 1982) instead of direct measurement of stomata conductance.…”
Section: Breeding For Dehydration Avoidancementioning
confidence: 99%
“…Whether these thresholds relate to the canopy conductance under well-watered conditions is an important question to resolve. Whether these canopy conductance differences would also relate to genotypic differences in transpiration efficiency [TE], which is a major source of crops yield variation under drought stress (Condon et al 2004;Sheshshayee et al 2006;Krishnamurthy et al 2007), is another one. None of these questions has been tested in cowpea and they are addressed in here.…”
Section: Introductionmentioning
confidence: 99%
“…A strong and positive relationship between SCMR and WUE was reported (Sheshshayee et al, 2006). SCMR and SLA are negatively correlated (Nageswara Rao et al, 2001;Upadhyaya, 2005) and genetic variation for SCMR has also been reported (Upadhyaya, 2005).…”
Section: Introductionmentioning
confidence: 99%